Stressful task increases drive for thinness and bulimia: a laboratory study - Sassaroli, Sandra; Fiore, Francesca; Mezzaluna, Clarice; Ruggiero, Giovanni Maria (Frontiers in Psychology, 2015)
The scientific literature has suggested that stress undergirds the development of eating disorders (ED). Therefore, this study explored whether laboratory induced stress increases self-reported drive for thinness and bulimic symptoms measured via self-report. The relationship between control, perfectionism, stress, and cognition related to ED was examined using correlational methodology. 86 participants completed an experimental task using a personal computer. All individuals completed a battery of tests before and after the stressful task. Analyses showed a significant statistical increase in average scores on the drive for thinness and bulimia measured before and after a stressful task, and path analysis revealed two different cognitive models for the mechanism leading to drive for thinness and bulimia. These findings suggest that stress is an important factor in the development of the drive for thinness and bulimia.